Revision of the Australopapuan and West Pacific species of plain pumpkin-beetles, the Aulacophora indica species-complex (Coleoptera: Chrysomelidae: Galerucinae) - Reid, Chris; Halling, Luke; Beatson, Max (Zootaxa, 2021)
The ‘plain pumpkin-beetle’, indica species-complex of Aulacophora Chevrolat, 1836, is revised for Australopapua, Timor and the West Pacific. The species-complex is defined and the following eight included species are diagnosed and described: A. abdominalis (Fabricius, 1781); A. barrogae Reid, Halling & Beatson, sp. nov.; A. cornuta Baly, 1879; A. indica (Gmelin, 1790); A. mbabaram Reid, Halling & Beatson, sp. nov.; A. relicta (Boisduval, 1835); A. wallacii Baly, 1886; A. wilsoni Baly, 1888. The three other similar species in the region of interest, A. bicolor (Weber, 1801), A coffeae (Weber, 1801) and A. deplanchei (Perroud & Montrouzier, 1864), are diagnosed from the Aulacophora indica species-complex and a key is provided for all 11 species. New synonyms are noted as follows (senior synonym first): A. abdominalis (Fabricius, 1781) = A. argyrogaster (Montrouzier, 1861) syn. nov., = A. fabricii Baly, 1886 syn. nov., = A. armigera Baly, 1889 syn. nov., = A. aruensis (Weise, 1892) syn. nov., = A. fauveli Beenen, 2008 syn. nov.; A. relicta (Boisduval, 1835) = A. palmerstoni Blackburn, 1888 syn. nov., = A. imberbis Weise, 1916 syn. nov.. Aulacophora relicta (stat. rev.) is revalidated from synonymy with A. abdominalis and A. wilsoni (stat. rev.) is revalidated from synonymy with A. scutellata (Boisduval 1835). Aulacophora flava Olivier, 1808, is not an available species name. The synonymy of A. robusta Duvivier, 1884 with A. cornuta is confirmed. Five species traditionally placed in Aulacophora, Galleruca flaveola Boisduval, 1835, G. punctata Boisduval, 1835, G. scutellata Boisduval, 1835, Galleruca flavescens Montrouzier, 1856 and Galleruca artensis Montrouzier, 1861, are not identifiable to genus or species and are therefore listed as nomina dubia within Galerucinae. The previously designated lectotype of A. abdominalis is shown to be invalid. Neotypes are created for A. abdominalis and A. relicta as both lack original type material. A lectotype is designated for A. palmerstoni. The plain pumpkin-beetle species are distributed as follows: A. barrogae, A. mbabaram, A. relicta and A. wilsoni are endemic to Australia; A. abdominalis is widespread in the southwestern Pacific and Melanesia, west to Timor and east to Niue, but is absent from mainland Australia; A. cornuta is widespread from eastern India to Melanesia as far east as Guadalcanal; A. indica is widespread from India southeast to Timor and northeast to Guam, and adventitious further south and east, but absent from, or not established in, Australia, Fiji, New Caledonia, Niue, Samoa, Tonga and Vanuatu; A. wallacii is endemic to Timor. Native hosts are unknown for any species, but A. abdominalis, A. indica, A. relicta and A. wallacii are pests of exotic cucurbit crops.